Pengaruh Latihan Bent Over Throw dengan Ball Flip Terhadap Peningkatan Power Lengan - Nurhidayanto, Davit; Sutisna, Nana; Rohendi, Andang (Jurnal Keolahragaan, 2023)
The reliant variable in the title of this study is the principal objective, specifically arm power. Pre-trial configuration is the applied technique. The area and exploration subjects were Yos Sudarso Kawunganten Center School understudies and Cilacap Rule. The method for taking the exploration object was absolute examining so there were 30 male understudies. The test offered to these understudies is the chance put toss test. The aftereffects of the review are: 1. The twisted-around toss practice essentially affects positive changes in the dangerous force of the arm muscles. 2. Ball flip activities fundamentally affect positive changes for the unstable force of the arm muscles. 3. There is a huge distinction between the twisted-around toss and ball flip activities for positive changes in the dangerous force of the arm muscles. Conclusion: Twisted-around toss and ball flip activities essentially affect expanding arm power in understudies of SMP Yos Sudarso Kawunganten, Cilacap Regime.